2001
DOI: 10.1023/a:1012313408062
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The activities of nuclear enzymes involved in NAD+ metabolism in Saccharomyces cerevisiae strain 913a-1 and its mutant 110 previously selected as an NAD+ producer were investigated. The presence of extracellular nicotinamide increased the total NAD+ pool in the cells and increased [3H]nicotinic acid incorporation; however, NAD+ concentration in isolated nuclei decreased slightly. The stimulating effect of nicotinamide on intracellular synthesis of NAD+ correlated with increases in ADP-ribosyl transferase, NAD+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Thus, based on the results, it can be confirmed that the increase in the intracellular NAD concentration in the local yeast strain S. cerevisiae 913a-1 that was observed by us earlier [7] is due to the presence of cytoplasmic proteins that possess enzymatic activity for transforming 3-MP into NA.…”
supporting
confidence: 81%
“…Thus, based on the results, it can be confirmed that the increase in the intracellular NAD concentration in the local yeast strain S. cerevisiae 913a-1 that was observed by us earlier [7] is due to the presence of cytoplasmic proteins that possess enzymatic activity for transforming 3-MP into NA.…”
supporting
confidence: 81%